Learn versus Earn: A case for the small business employers and those fresh graduates who join them - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
Go to university. Collect scroll. Join a multinational corporation. Prosper. Advance to Go. Collect $200. Newly minted graduates, venturing beyond the comforts of the ivory towers for the very first time, can often hold strong views on what 'the outside world' has to offer, and how that might subsequently colour their future. Join a big international conglomerate and earn bragging rights. Join a 'boutique' outfit (read: sweatshop) and, well, blame the economy. Such sentiments present employers of small-and-medium enterprises (SMEs) with the short end of the stick. One successful SME employee-turned-employer would argue, however, that it is the fresh graduate who has got the wrong end of the stick.